Description of larva and female of Polypedilum (Probolum) bullum Zhang & Wang with DNA barcodes - Lei, Qi; Chen, Jinxian; Song, Chao; Qi, Xin; Zhang, Ruilei (Zootaxa, 2020)
The larva and female of Polypedilum (Probolum) bullum Zhang & Wang associated with morphological characteristics and DNA barcodes are described and illustrated for the first time. The female is characteristic with developed dorsomesal lobe and ventrolateral lobe both densely covered with apical setae, ventrolateral lobe partially covered by dorsomesal lobe. The larva is distinguished by the shape of mentum, pecten epipharyngis, labral SI and labral SII.